Metabolic adaption of cancer cells toward autophagy: Is there a role for ER-phagy? - Gentile, Debora; Esposito, Marianna; Grumati, Paolo (Frontiers in Molecular Biosciences, 2022)
Autophagy is an evolutionary conserved catabolic pathway that uses a unique double-membrane vesicle, called autophagosome, to sequester cytosolic components, deliver them to lysosomes and recycle ammino-acids. Essentially, autophagy acts as a cellular cleaning system that maintains metabolic balance under basal conditions and helps to ensure nutrient viability under stress conditions. It is also an important quality control mechanism that removes misfolded or aggregated proteins and mediates the turnover of damaged and obsolete organelles. In this regard, the idea that autophagy is a non-selective bulk process is outdated. It is now widely accepted that forms of selective autophagy are responsible for metabolic rewiring in response to cellular demand. Given its importance, autophagy plays an essential role during tumorigenesis as it sustains malignant cellular growth by acting as a coping-mechanisms for intracellular and environmental stress that occurs during malignant transformation. Cancer development is accompanied by the formation of a peculiar tumor microenvironment that is mainly characterized by hypoxia (oxygen <2%) and low nutrient availability. Such conditions challenge cancer cells that must adapt their metabolism to survive. Here we review the regulation of autophagy and selective autophagy by hypoxia and the crosstalk with other stress response mechanisms, such as UPR. Finally, we discuss the emerging role of ER-phagy in sustaining cellular remodeling and quality control during stress conditions that drive tumorigenesis.